Clinical presentation and predictors of survival related to extent of bone metastasis in 900 prostate cancer patients. (2nd September 2016) - Klaff, Rami; Varenhorst, Eberhard; Berglund, Anders; Hedlund, Per Olov; Sjöberg, Folke; Sandblom, Gabriel; ,
Abstract: Objective: The aim of this study was to investigate the impact of bone metastasis on survival and quality of life (QoL) in men with hormone-naïve prostate cancer. Materials and methods: The study included 900 patients from a randomized trial (No. 5) by the Scandinavian Prostate Cancer Group, comparing parenteral oestrogen with total androgen blockade. Extent of bone metastasis was categorized according to a modified Soloway score: score 1, n = 319; score 2, n = 483; and score 3, n = 98 patients. The primary outcome measurements were mean differences in QoL and overall survival. Results: QoL rating scales showed a decrease with increasing extent of bone metastasis ( p < 0.001). The mean global health status decreased from 64.4 to 50.5 for Soloway score 1 and 3, respectively. Following adjustment for performance status, analgesic consumption, grade of malignancy, alkaline phosphatase, prostate-specific antigen, haemoglobin and global health status, Soloway score 2 and 3 had a 47% [hazard ratio (HR) 1.47, 95% confidence interval (CI) 1.21–1.80] and 78% (HR 1.78 95%, CI 1.32–2.42) increased mortality, respectively, compared to Soloway score 1. Independent predictive factors of mortality were assessed. Conclusions: Patient grouping based on three categories of extent of bone metastasis related to performance status, haemoglobin and global health status at presentation, as independent predictors of mortality, may provide improved accuracy of prognosis.